Combined use of statins and inhibitors of arginase l-norvaline for correcting endotoksin-inducing endotelial dysfunction - T. A. Denisyuk; M. V. Pokrovsky; G. A. Lazareva; T. G. Pokrovskaya; M. V. Korokin; O. A. Osipova; A. I. Lazarev; L. N. Sernov; S. A. Demchenko (Кубанский научный медицинский вестник, 2016)
Using of the combined use of non-selective inhibitor of arginase L-norvaline with simvastatin, atorvastatin, rosuvastatin and rosuvastatin nanopartikulirovanny on background modeling endotoxin-induced disease, the introduction of strain 603 Staphylococcusaureus shows ekdotelio- and cardioprotective effects, manifested in preventing the proliferation of coefficient of endothelial dysfunction (CED), adrenoreactivity, maintaining myocardial reserve and normalization values of biochemical markers (Total NO, Expression of eNOS, C-reactive protein, IL-6, TNF). Thus, combination therapy found no additive effect of drugs.